1986
DOI: 10.1099/0022-1317-67-7-1435
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus IBV: Virus Retaining Spike Glycopolypeptide S2 but Not S1 Is Unable to Induce Virus-neutralizing or Haemagglutination-inhibiting Antibody, or Induce Chicken Tracheal Protection

Abstract: SUMMARYAvian infectious bronchitis coronavirus (IBV) inactivated by fl-propiolactone induced partial protection of the trachea in up to 40~ of chickens following one intramuscular inoculation 4 to 6 weeks prior to challenge. Retention of an intact tracheal ciliated epithelium 4 days after challenge was the criterion of protection. There was no correlation between protection and serum titres of virus-neutralizing (VN) and haemagglutination-inhibiting (HI) antibody, which were maximal at about 4 weeks after inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
139
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(145 citation statements)
references
References 20 publications
6
139
0
Order By: Relevance
“…For example, we have shown that the anti-F3 serum does not contain any detectable virus-neutralizing activity. It should be borne in mind that the anti-F3 serum was produced using an antigen synthesized in bacteria but, nevertheless, this result correlates with the conclusions of Cavanagh et al (1986) who proposed that neutralizing epitopes on the coronavirus S protein are located within the amino-terminal S1 polypeptide. Finally, the strategy described here may be useful in characterizing further coronavirus nonstructural proteins.…”
Section: Discussionsupporting
confidence: 64%
“…For example, we have shown that the anti-F3 serum does not contain any detectable virus-neutralizing activity. It should be borne in mind that the anti-F3 serum was produced using an antigen synthesized in bacteria but, nevertheless, this result correlates with the conclusions of Cavanagh et al (1986) who proposed that neutralizing epitopes on the coronavirus S protein are located within the amino-terminal S1 polypeptide. Finally, the strategy described here may be useful in characterizing further coronavirus nonstructural proteins.…”
Section: Discussionsupporting
confidence: 64%
“…Major glycoprotein species of 100K and 120K were more often revealed by SDS-PAGE than the 200K component, but were antigenically related. They may have been derived from the 200K species by proteolytic cleavage, as reported for other coronaviruses (Sturman et al, 1985 ;Cavanagh et al, 1986a). The reactivity of anti-gp200/100 MAbs with intracellular polypeptides corresponding to an approximate M~ of 170K to 180K, 120K and 90K also suggested a close relationship among these components.…”
Section: Discussionmentioning
confidence: 63%
“…The peplomeric E2 glycoprotein is often cleaved post-translationally by host cell proteases into two 85K to 100K subunits (Sturman et al, 1985;Cavanagh et al, 1986b). The latter also is known to be responsible for virus attachment and cell membrane fusion (Collins et al, 1982), and elicits the production of virus-neutralizing antibodies (Fleming et al, 1983;Laude et al, 1986;Niesters et al, 1987; which may be protective (Buchmeier et al, 1984;Wege et al, 1984;Cavanagh et al, 1986a). An additional glycoprotein of 130K to 140K, a disulphide-linked dimer of 65K subunits, is associated with the haemagglutinin (E3) of viruses belonging to the subgroup of haemagglutinating mammalian coronaviruses (King et al, 1985 ;Hogue & Brian, 1986: Sugiyama et al, I986).…”
Section: Introductionmentioning
confidence: 99%
“…The spike protein is the major inducer of neutralising antibody (Cavanagh et al, 1984) and has been implicated in the induction of protective immunity. Thus whereas the intramuscular inoculation of inactivated'IBV induced some resistance to challenge in the trachea of chickens there was no such resistance in chickens that had been inoculated with virus from which SI, but not any other protein, had been removed (Cavanagh et al, 1986b). Also, inoculation of SI alone did result in the production of virus neutralising antibody.…”
Section: Discussionmentioning
confidence: 90%